Genomic characterisation of environmental Pseudomonas aeruginosa isolated from dental unit waterlines revealed the insertion sequence ISPa11 as a chaotropic element. Issue 9 (26th August 2017) - Vincent, Antony T.; Freschi, Luca; Jeukens, Julie; Kukavica-Ibrulj, Irena; Emond-Rheault, Jean-Guillaume; Leduc, Annie; Boyle, Brian; Jean-Pierre, Fabrice; Groleau, Marie-Christine; Déziel, Eric; Barbeau, Jean; Charette, Steve J.; et al.
Abstract: The bacterium Pseudomonas aeruginosa is well known to have a remarkable adaptive capacity allowing it to colonise many environments. A recent study on environmental isolates from dental unit waterlines (DUWLs) hinted at a genetic clustering into two groups. Isolates from one of these groups, named cluster III, were shown to have unusual phenotypes for environmental isolates, such as an increased biofilm production. To have a better ecological view, more specifically on isolates from cluster III, the complete genomes of 39 isolates including 16 from DUWLs were sequenced. In addition to an investigation of antibiotic resistance and secretion system gene content, a molecular phylogeny allowed confirmation of the split of the 16 environmental isolates in two groups and also sheds light on a correlation between the phylogenetic positions and the serotypes of the isolates. Isolates from cluster III harboured insertion sequences IS Pa11 inserted into the O-specific antigen biosynthesis clusters and the gene lasR, encoding for a master regulator of the quorum sensing. Investigation of key regulators revealed another truncated gene, gacS . Alteration in lasR and gacS genes was consistent with phenotypic assays confirming their inactivation. These results bring new perspectives regarding the ecological adaptive potential of P. aeruginosa . Abstract : This study sheds light on a phylogenomics dichotomy between dental unit waterlines and clinical isolates of Pseudomonas aeruginosa .